The clinical utility of normal range carbohydrate antigen 19-9 level as a surrogate marker in evaluating response to treatment in pancreatic cancer—a report of two cases - Al-Shamsi, Humaid O.; Alzahrani, Mohammed; Wolff, Robert A. (Journal of Gastrointestinal Oncology; Vol 7, No 3 (June 01, 2016): Journal of Gastrointestinal Oncology, 2016)
Carbohydrate antigen 19-9 (CA 19-9) is a tumor marker that is has been has been intensely studied and investigated as a surrogate marker in pancreatic cancer (PC). It is also commonly utilized in the clinical management of PC. We report two cases where normal range CA 19-9 level has been shown to be useful as a surrogate marker for following PC progression and response to treatment. Initially in our cases, both patients had a resectable tumor and their tumor markers were within normal range. In both cases the normal range CA 19-9 increase from the baseline was associated with corresponding progressive disease on imaging studies and CA 19-9 decline was in keeping with response to systemic and local therapy despite being within the normal range. To our knowledge, this is the first case report where we report the utility of serial normal values of CA 19-9 as a useful tool in following PC disease activity and in response to treatment. Clinicians should consider measuring serial normal values of CA 19-9 in patients with PC and normal range CA 19-9 which may help in assessing response to treatment in subset of this population.